A legal study on the criminalization of sexual service purchase in Malaysia under the Penal Code (ACT 574) / Ahmad Fadhli Ramlan - Ramlan, Ahmad Fadhli (2017)
This study involves the main issue of prostitution in Malaysia. The current scenario related to prostitution most likely seen as an endless issue. This study try to examine the problem in Malaysia and compared it another jurisdiction which is Sweden. It was a different approach taken into action but at least it’s a good policy even it was not abolished the prostitution issue in total. The regulation of the prostitution under the Penal Code (Act 574) can be describe generally inadequate to prevent and reduce the problem itself. Therefore the research question and objective of this paper will highlight on the lacuna that exist in the Penal Code (Act 574) which are lead to inadequate to deter those who purchase the sexual services. Hopefully this will give a kick start to the policy maker in Malaysia to look at the different perspective on the idea raised in this study then rectify the weaknesses. Explicitly the Acts are referred throughout the research, with limited comparative study on the related laws of Sweden. A qualitative approach was adopted with concentration on doctrinal research combined with fieldwork. Due to some limitation and constraints, the doctrinal research mainly concentrated in library based research that covered various literatures and related Acts. Semi structured interviews had been carried out with selected individuals having the necessary experience and competent authority. As a conclusion, the result of the research corresponds to the objective and answered most of the queries but the implementation to the proposal may be involved some technical issue that may be need further review.